Computing and the Internet - Kavanaugh, Beatrice (Broomall, Pennsylvania Mason Crest, 2017)
Since it became widely available for public use in the early 1990s, the Internet has proven to be amazingly useful for facilitating communication, distributing information, and sharing knowledge. Human society has already been changed by the Internet, and as new technologies develop, even more opportunities will be available to people online. However, some people have concerns about technology and privacy, the availability of new technology to everyone, and whether information shown on the web might influence people or cultures in a negative way. This book looks at the role that the Internet and computer technologies play in society, and considers some of the questions that are raised by its development.
History of the digital revolution -- Current advances in digital technology -- Economic and social impact -- Regulating digital content -- Moving toward the future.
Includes bibliographical references (pages 75-76) and index.
8 - 12 years
105945
Keywords: Internet -- Social aspects -- Juvenile literature; Computers -- Social aspects -- Juvenile literature; Information technology -- Social aspects; Computers -- Social aspects; Information technology -- Social aspects; Computer science; Juvenile works